PENGARUH PENGGUNAAN MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR PENJUMLAHAN DAN PENGURANGAN PECAHAN DI KELLAS V SDN 14 AUR TAJUNGKANG TANGAH SAWAH (ATTS) BUKITTINGGI - Hafizah, Nadra; Zainil, Melva; Indrawati, Tin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractThis study aims to determine the effect of the used of the Teams Game Tournament type (TGT) cooperatif model on the learning result of addition and subtraction of frantion on grade 5th elementary school14 AurTajungkang Tangah Sawah (ATTS) Bukittinggi. This research design is quasi experiment with nonequivalent control group design. The sample in this study is grade5A SDN 14 ATTS as the Exsperiment class and grade 5B  as Control class. The results showed that   of the used of the Teams Game Tournament type (TGT) cooperatif model on the learning result of addition and subtraction of frantion on grade 5th elementary school14 AurTajungkang Tangah Sawah (ATTS) Bukittinggi. This is evidenced by the results of tcount4,06593 and t table at a significance level of 0.05 at 1.6725, so that t count> t table.  Keyword :The Addition and Subtraction of Fraction, TGT